Evaluation of pathological parameters and morphometric data of desmoplastic lobular breast carcinoma - Ivan R Ilic; Nikola M Stojanović; Pavle J Randjelović; Marina N Mihajlović; Niko S Radulović; Ratko S Ilić (Wolters Kluwer Medknow Publications, 2016)
Background: Invasive lobular breast cancer (ILC) is the second most frequent form of breast cancer. While cancer cells are regularly investigated, tumor stroma represents a highly unexplored field. Aims: The aim of this study is to perform a detailed investigation of clinical, immunohistochemical, and morphometric characteristics of desmoplastic (D) and nondesmoplastic (ND) ILC. Materials and Methods: This study included twenty cases of ILC that were divided into two groups designated as D and ND groups. Medical histories and diagnosis data were obtained from the archives of the Center of Pathology, Clinical center Niš (Serbia). Morphometric analysis of hematoxylin and eosin stained slides was performed using ImageJ software, and the obtained data were further statistical processed. Results: Statistical analyses of the data revealed that no significant differences between D and ND groups when patient age, estrogen receptor (ER), and progesterone receptor (PR) expressions and morphometrical parameters (such as the distance between groups of cancer cells and nucleocytoplasmic ratio) were compared. However, D and ND groups statistically, significantly differed in the occurrence of axillary lymph node metastasis, and when the ER and PR data were included, in certain nuclear parameters (cell/nucleus area, perimeter, Feret's diameter, and circularity). Conclusions: Desmoplastic stroma was observed more frequently in patients without axillary lymph node metastases, whereas the expression of ER and PR had no influence on its development. According to the measured morphometric parameters larger cells/nuclei belonged to ND group.